Peculiarities of the digital and sustainable development of chinese civil blasting industry enterprises - Kopishynska, K.; Yang, W. (Економічний вісник Донбасу, 2024)
The article is devoted to the study of the peculiarities of digital and sustainable development of enterprises of the civil blasting industry in China. The main economic results of enterprises in the industry over the past five years are analysed. A comparative analysis of the functioning of civil blasting enterprises in China and international enterprises is carried out. The key directions of introduction of digital technologies to ensure the development of enterprises in the industry are identified. The necessity of using sustainable blasting methods to comply with regulatory standards in accordance with the China Sustainable Development Plan is substantiated. The article is devoted to the study of the peculiarities of digital and sustainable development of enterprises of the civil blasting industry in China. The main economic results of enterprises in the industry over the past five years are analysed. A comparative analysis of the functioning of civil blasting enterprises in China and international enterprises is carried out. The key directions of introduction of digital technologies to ensure the development of enterprises in the industry are identified. The necessity of using sustainable blasting methods to comply with regulatory standards in accordance with the China Sustainable Development Plan is substantiated.